2013
DOI: 10.1371/journal.pone.0060320
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel, Cisplatin and Fluorouracil (DCF) Regimen Compared with Non-Taxane-Containing Palliative Chemotherapy for Gastric Carcinoma: A Systematic Review and Meta-Analysis

Abstract: BackgroundGastric carcinoma (GC) is one of the highest cancer-mortality diseases with a high incidence rate in Asia. For surgically unfit but medically fit patients, palliative chemotherapy is the main treatment. The chemotherapy regimen of docetaxel, cisplatin and 5-fluorouracil (DCF) has been used to treat the advanced stage or metastatic GC. It is necessary to compare effectiveness and toxicities of DCF regimen with non-taxane-containing palliative chemotherapy for GC.MethodsPubMed, EmBase, Cochrane Central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 44 publications
4
29
1
Order By: Relevance
“…It is interesting to emphasize that the REAL-2 phase III clinical trial that led to the generalization of EOX in AGC confirmed the non-inferiority hypothesis for oxaliplatin and capecitabine versus cisplatin and fluorouracil; however, the study was not designed to appraise the value of adding epirubicin, since the four treatment arms included anthracycline [24]. The role of adding anthracyclines to platinum and fluoropyrimidine-based schedules is even more controversial if we consider that docetaxel-containing triplets have demonstrated their superiority to doublets not containing docetaxel in a multicenter, phase III study [25] and have achieved an increase in responses and a trend toward greater survival rates in a meta-analysis that included 12 RCTs [26]. Likewise, triplets with docetaxel have displayed a trend toward superiority over triplets with anthracyclines (NCT02445209) [27].…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to emphasize that the REAL-2 phase III clinical trial that led to the generalization of EOX in AGC confirmed the non-inferiority hypothesis for oxaliplatin and capecitabine versus cisplatin and fluorouracil; however, the study was not designed to appraise the value of adding epirubicin, since the four treatment arms included anthracycline [24]. The role of adding anthracyclines to platinum and fluoropyrimidine-based schedules is even more controversial if we consider that docetaxel-containing triplets have demonstrated their superiority to doublets not containing docetaxel in a multicenter, phase III study [25] and have achieved an increase in responses and a trend toward greater survival rates in a meta-analysis that included 12 RCTs [26]. Likewise, triplets with docetaxel have displayed a trend toward superiority over triplets with anthracyclines (NCT02445209) [27].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the non-inferior efficacy, oxaliplatin may be substituted for cisplatin in the treatment of AGC, and elderly patients may derive a particular benefit from treatment with oxaliplatin instead of cisplatin (10,14). Taxanes, such as docetaxel or paclitaxel, which bind and stabilize microtubules and therefore lead to cell-cycle arrest, have also been used as a first-line therapy for AGC (15,16). In addition, irinotecan has been reported to demonstrate activity in gastrointestinal cancers, and irinotecan-based combination regimens have been studied as a first-line alternative to platinum-based chemotherapy (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…However, if sequential treatment with all active cytotoxic agents cannot be guaranteed for 100% of the patients, the use of a triplet combination protocol may be considered as first-line therapy. The safety and efficacy of this approach has been assessed in previous clinical trials (15,16). Triplet combination chemotherapy comprising an anthracycline or a taxane in addition to fluoropyrimidine and platinum compounds has resulted in higher response rates and a modest improvement in overall survival compared with doublet combinations (6).…”
Section: Univariate Analysis Multivariate Analysis ------------------mentioning
confidence: 99%
“…The pretreatment characteristics of patients are listed in Table 1. None of the patients had previously received chemotherapy for advanced disease; 9 patients had received adjuvant chemotherapy without docetaxel or oxaliplatin with a median disease-free interval of 12 months (range, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] (Figs. 1, 2).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…The incorporation of docetaxel to cisplatin/fluorouracil chemotherapy (DCF) showed superiority over cisplatin/fluorouracil in a randomized phase III trial [8]. Furthermore, in a recent meta-analysis the use of DCF was correlated with a higher response rate than non-taxanes-containing regimens [13]. Nevertheless, the widespread use of DCF was hindered by severe toxicity, such as neutropenic infections and febrile neutropenia.…”
Section: Introductionmentioning
confidence: 99%